Histopathological changes of parotid and larynx in hypothyroid rats: experimental study - ÖZBEYLİ, DİLEK (SPRINGER, 2022)
Objectives In this study, we aimed to investigate the laryngeal and parotid histopathological alterations in rats with experimentally induced postnatal hypothyroidism. Materials and methods 200-300 g weighed Wistar albino rats were included in this study. The rats were randomly divided into four groups: group 1 is control and the other groups are experimental groups. Food and water were supplied ad libitum in group 1, no medication was administered. Propylthiouracil (PTU) was administered intraperitoneally for 15 days in group 2; for 30 days in group 3, for 45 days in group 4. The larynx and parotid glands of the rats were removed and intracardiac blood samples were collected for thyroid-stimulating hormone (TSH) analysis under anesthesia (ketamine hydrochloride, 100 mg/kg) 24 h after the last PTU injection. The same procedures were done for the control group at day 46. Histopathological evaluation was done for all the specimens. Results While submucosal vascular dilatation was significantly higher in the experiment groups (p < 0.05), there was not a significant difference in lamina propria edema, inflammation, goblet cell loss, cilia loss between the groups in larynx specimens. In parotid gland specimens, serous asinus atrophy, stromal connective tissue increase were significantly higher in experiment groups (p < 0.05). In addition, there was a significant difference in nuclear morphology between control and experimental groups (p < 0.05). Conclusion The results of the study showed that hypothyroidism may have effect on inflammatory procedure by causing vascular dilation in larynx and serous asinus atrophy nucleus changes, connective tissue increase in stroma in parotid gland.
Keywords: Hypothyroidism; Rat; Larynx; Parotid; Xerostomia; Reinke's edema; Hoarseness; BRAIN